Identification of Occupational Health and Safety of Formwork Using the Job Safety Analysis Method of Building Construction Projects - Regita Gusttriana; Sely Novita Sari; Anggi Hermawan (Universitas Islam Raden Rahmat, Malang, 2026)
Formwork in construction projects has a high level of risk to worker safety due to heavy material handling, equipment use, and activities at height. This study will investigate potential hazards in formwork through Job Safety Analysis (JSA) and assess the effectiveness of risk control based on the Hierarchy of Control, which includes elimination, substitution, engineering control, administrative control, and the use of personal protective equipment (PPE). Data collection was executed via on site observations, evaluation of project K3 documentation, and conversations with safety officers, supervisors, and associated workers. The results of the analysis indicated that risk control was more applied to engineering control (55.1%), administrative control (20.4%), and the use of PPE (20.4%). Meanwhile, of substitution (4.08%) and elimination (0%) are still very low. This condition shows that the control with the highest level of effectiveness has not been maximized, so the potential risk of accidents remains high. The findings emphasize the value of implementing top-level controls from the planning and design stages of the project. The use of Hierarchy of Control-based Job Safety Analysis has proven to be a systematic approach in determining risk control priorities and improving occupational safety management. Thus, the results of this study provide strategic recommendations for construction projects in minimizing accidents and building a more effective safety culture.